Enzyme-responsive polymers for microbial infection detection. (November 2015) - Schiffer, Doris; Tegl, Gregor; Heinzle, Andrea; Sigl, Eva; Metcalf, Dan; Bowler, Philip; Burnet, Michael; Guebitz, Georg M
Abstract : There is a pressing need for point-of-care diagnostics indicating early stages of infection. Polymers can respond to enzymes secreted by microorganisms or released by the human immune system. This provokes either a direct color reaction or release of dyes, allowing early-stage detection of wound infections and contamination of medical devices. Conventional methods for the detection of infection indicators are based on slow, laboratory-based procedures and, consequently, do not allow a timely assessment. In contrast, polymer-based materials offer real-time responses in point-of-care devices that, in turn, allow therapists to amend treatment before the infection has become firmly established. The use of protein, polysaccharide and mixed polymer systems provides a sensitive means to detect the low levels of proteases and glycosyl hydrolases produced on initiation of infection in the clinical setting. These polymers can be easily fabricated into various forms that can be directly applied in diagnostic devices.